PENERAPAN KESEHATAN DAN KESELAMATAN KERJA PADA PERAWAT DI RUMAH SAKIT: LITERATURE REVIEW - Prasetyawati; Hariawan, Hamdan (Poltekkes Kemenkes Bengkulu, 2024)
Nurses as health workers play a role in providing nursing services to patients for 24 hours continuously in hospitals. Nurses are also workers who receive higher potential hazards than other health workers in the hospital. This literature review aims to identify factors that influence the implementation of occupational safety and health (SMK3) in nurses in hospitals. The writing of this article uses the literature review method by collecting several articles from the Google Scholar database in the period 2021-2024. From the results of the review of five literatures, it shows that there are several factors that influence the application of SMK3 to nurses in hospitals, namely knowledge, attitudes, actions, education levels, and nurses' work adaptability to the work environment. Whether or not the application of SMK3 for nurses in hospitals depends on internal factors in the form of nurses' behavior and external factors in the form of nurses' education level and work environment.